PERTANGGUNGJAWABAN PIDANA ANAK TERHADAP KASUS PEMBUNUHAN YANG DILAKUAN TERHADAP IBU KANDUNG DI WILAYAH HUKUM PENGADILAN NEGERI ATAMBUA, KABUPATEN BELU (STUDI TERHADAP PUTUSAN NOMOR:3/PID.SUS/2019/PN.ATB) - Asa, Rynaldo Jonathan Belka Asoli; Amalo, Heryanto; Kian, Darius A (Petitum Law Journal, 2023)
A criminal case of murder committed by a child against the biological mother which occurred in Manu Mutin Sub-district, Atambua City Sub-district, Belu district. The researcher formulated two main problems, namely, what is the criminal responsibility of chidren who commit the crime of mudering their biological monther in the jurisdiction of the Atambua District Court, Belu Regebcy? And what are the efforts to deal with cases of chid murder of biological mother in Manu Mutin sub-district, Atambua City sub-district, Belu district?. From the result of the research, a conclusion was made abaout criminal responsibility by testing the ability to be responsible where the child was aware of his actions and in the trial no justification or excuse was faound and in proving guilt it was seen from the elements of the act and the element of intent and the countermeasures applied were penal efforts where the child was sentenced. Improsonment and job training in kupang children’s prison as well as charging children court costs. The next effort is a non-penal effort through a legal education program related to juvenile crime. So the suggestions rposed regarding criminal responsibility for children must pay more attention to the provisions set out in law number 11 of 2012 and law enforcers play an active and increased role in carrying out educational outreach to te general public.